On the Dominance of Deformation in Nuclear Physics, its Link to Symplectic Symmetry, and its Roots in an Effective Field Theory - Draayer, J.; Kekejian, D.; Sargsyan, G.; Dydtrych, T.; Baker, R.; Launey, K. (HNPS Advances in Nuclear Physics, 2022)
A brief historical review of the important role symmetries have played in our gaining a deeper understanding nuclear structure is presented.We then focus our attention on the special role that symplectic symmetry plays in exposing a “Dominance of Deformation” that is found through enhanced B(E2) rates across the Chart of the Nuclides, and in addition, we will show how the No-Core Symplectic Shell Model (NC-SpSM) seems to emerge from a Symplectic Effective Field Theory(Sp-EFT), where the latter prepares away forward for gaining a truly ab initio understanding of the structure of atomic nuclei. As space permits, various spectra, B(E2) transition rates, and nuclear radii of selected light to medium-mass nuclei are shown.